Mullite rod-enhanced porous SiC ceramics prepared at low temperature from photovoltaic waste. Issue 15 (December 2018) - Xing, Zhiheng; Xiang, Daoping; Ma, Yanping
Abstract: In this paper, porous SiC ceramics (PSCs) were fabricated from photovoltaic waste at low temperatures. The effects of different additives and sintering temperatures on PSCs were studied in detail. The temperature of PSCs preparation can be reduced to 850 °C by adding MoO3 as catalyst. The PSCs are reinforced by mullite rods grown in-situ, they also have a high permeability coefficient due to their network structure. From 850 °C to 1200 °C, the open porosity of PSCs changed slightly, and was within 45.32 ± 0.6%. The PSCs produced at 1000 °C had the highest gas permeability coefficient of 8.24 × 10 –11  m 2 and the highest flexural strength of 50.17 MPa. However, the same PSCs could not be fabricated at 850 °C when Y2 O3 or CeO2 were used as sintering aids. This study provides an environment-friendly method for reusing photovoltaic waste and reducing the cost of preparing PSCs.